Correlation between the performance of taekwondo athletes in an Adapted Anaerobic Kick Test and Wingate Anaerobic Test - Paulino Oliveira, M.; Szmuchrowski, L. A.; Arruda Gomes Flor, C.; Goncalves, R.; Pena Couto, B. (Archives of Budo Conference Proceedings, 2015)
Background & Study Aim: To characterize the energy demands of taekwondo, researchers have verified the relevant contribution of anaerobic energy supply to athletes during fights. To evaluate anaerobic capacity, the Wingate Anaerobic Test (WAnT) was developed, which is based on the use of the lower limbs. For assessing anaerobic power using a more specific taekwondo technique, an adapted test was created, Adapted Anaerobic Kick Test (AAKT), which consists of a repeated execution of the kick technique banda chagui. A comparison between the results of these tests allows a verification of the validity of the utilization of WAnT as a task for assessing performances in taekwondo. The aim of this study was to correlate the results between WAnT and AAKT for the lower limbs. Material and Methods: The study included 15 individuals (10 males and 5 females), all of them Brazilian taekwondo athletes from UFMG Sports Training Center (mean age 20.17 ± 1.89 years), mean body mass (63.82 ± 9.22 kg) and mean height (170.08 ± 9.87 cm). Results: A significant correlation was founded in the comparison between the WAnT and AAKT results. It was founded a strong correlation between three parameters, the relative peak power and higher kick frequency, index fatigue WAnT and index fatigue AAKT, and relative average power and average kick frequency. Conclusion: These findings identified the WAnT is appropriate for assessing peak anaerobic power and capacity of taekwondo competitors.